2020
DOI: 10.1177/1533033820983029
|View full text |Cite
|
Sign up to set email alerts
|

SLC6A8 Knockdown Suppresses the Invasion and Migration of Human Hepatocellular Carcinoma Huh-7 and Hep3B Cells

Abstract: Liver cancer is considered the sixth most commonly diagnosed cancer and the fourth leading cause of cancer-related deaths worldwide. Currently, there is no specific and effective therapy for hepatocellular carcinoma. Therefore, developing novel diagnostic and therapeutic strategies against hepatocellular carcinoma is of paramount importance. Solute carrier family 6 member 8 (SLC6A8) encodes the solute carrier family 6-8 to transport creatine into cells in a Na+ and Cl-- dependent manner. SLC6A8 deficiency is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The altered level and activity of creatine transporter can be connected with tumour development. Analysis of literature data showed that an elevated level of SLC6A8 was noticed in breast [ 55 ], non-small cell lung [ 50 ] or hepatocellular cancers [ 56 ]. In clinical trials, inhibition of CT-1 is tested for the treatment of colorectal carcinoma [ 57 ].…”
Section: Clinical Significance Of Slc6a6 and Slc6a8 Transportersmentioning
confidence: 99%
“…The altered level and activity of creatine transporter can be connected with tumour development. Analysis of literature data showed that an elevated level of SLC6A8 was noticed in breast [ 55 ], non-small cell lung [ 50 ] or hepatocellular cancers [ 56 ]. In clinical trials, inhibition of CT-1 is tested for the treatment of colorectal carcinoma [ 57 ].…”
Section: Clinical Significance Of Slc6a6 and Slc6a8 Transportersmentioning
confidence: 99%
“…In tumors, previous study has demonstrated that SLC6A8 is overexpressed in human liver metastases compared with primary colorectal tumors and associated with enhanced colorectal cancer cell survival during hypoxic stress, suggesting the protective effects of SLC6A8 in cancer cells. It was recently reported that SLC6A8 knockdown suppressed the invasion and migration of human hepatocellular carcinoma cells [ 17 ]. Nonetheless, the implications of SLC6A8 in tumor progression remain poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that creatine promotes cancer metastasis through activation of Smad2/3 ( 20 ). In addition, a study at the cellular level demonstrated that knockdown of SLC6A8 significantly induced apoptosis and inhibited migration and invasion of Hep3B and Huh-7 cells in hepatocellular carcinoma cells ( 21 ). Therefore, there is a promising research potential regarding SLC6A8 , however, fewer relevant reports exist in lung cancer.…”
Section: Introductionmentioning
confidence: 99%